Case report: Ultrasound and contrast-enhanced ultrasound findings of pediatric small intestinal inflammatory myofibroblastic tumor - Xing, Zengmiao; Wu, Tangna; Qin, Lingling (Frontiers in Oncology, 2025)
Inflammatory myofibroblastic tumors (IMTs) are uncommon mesenchymal neoplasms with malignant potential, primarily affecting children and adolescents. It usually manifests in the abdominal and pelvic regions; however, small intestinal IMT is particularly rare. This report presents the case of a 7-year-old girl who presented with a small intestinal IMT. The patient was admitted with a one-day history of abdominal pain and vomiting. Ultrasonography revealed a solid hypoechoic mass in the lower abdomen. Based on contrast-enhanced ultrasound (CEUS) findings, a preliminary diagnosis of small intestinal IMT was proposed, which was subsequently confirmed by postoperative histopathology. This case underscores the sonographic and CEUS features of small intestinal IMT in children, emphasizing that the combination of ultrasound and CEUS can improve diagnostic accuracy and preoperative evaluation in pediatric patients.